Modelling vaporous and gaseous cavitation in transmission lines - Chan, Yew Boon. (2013)
A comprehensive study on modelling vaporous and gaseous cavitation in transmission lines will be presented in this study. The purpose of this study is to develop a model to predict the effects of cavitation.